Understanding EFL Students’ Adoption of Generative AI for English Learning: An Integrated UTAUT2 Model and Self-determination Theory - Surachmi W, Sri; Solihati, Tri Agustini; Rahmatika, Laily; Musdalifah; Islam, M Monjurul; Haryanto, Sigit (Online Learning, 2025)
Despite the increasing use of generative artificial intelligence (GenAI) tools among students, limited research has examined the underlying mechanisms guiding their adoption in English as a Foreign Language (EFL) education. Drawing on the unified theory of acceptance and use of technology 2 (UTAUT2) and self-determination theory (SDT), this study examines the factors shaping Indonesian EFL students’ intention and actual use of GenAI for English learning. Using a cross-sectional survey design, data were collected using an online questionnaire from 462 EFL students at three private universities in Indonesia and analyzed with the partial least squares structural equation modeling (PLS-SEM) using SmartPLS 4. The results indicated that performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, habit, autonomy, and relatedness significantly impacted EFL students’ intention to adopt GenAI for English learning. While competence did not significantly influence behavioral intention, both the SDT components (autonomy, competence, and relatedness) and behavioral intention were predictors of actual usage. The integrated framework explained a high proportion of variance (R² = 83.1% for behavioral intention; R² = 77.1% for actual use). These insights advance understanding of the technological and motivational determinants of GenAI adoption in EFL education and offer evidence-based direction for designing effective, equitable, and ethically responsible AI-supported English learning practices.